Movement Competency Screens Can Be Reliable In Clinical Practice By A Single Rater Using The Composite Score - Kerry J. Mann; Nicholas O'Dwyer; Michaela R. Bruton; Stephen P. Bird; Suzi Edwards (International Journal of Sports Physical Therapy)
# Background